Identification of 5-hydroxytryptamine-producing cells by detection of fluorescence in paraffin-embedded tissue sections - Y. Kaneko; N. Onda; Y. Watanabe; M. Shibutani (European Journal of Histochemistry, 2016)
5-Hydroxytryptamine (5-HT) produced by enterochromaffin (EC) cells is an important enteric mucosal signaling ligand and has been implicated in several gastrointestinal diseases, including inflammatory bowel disease and functional disorders such as irritable bowel syndrome. The present study reports a new, simple and rapid visualization method of 5-HT-producing EC cells utilizing detection of autofluorescence in paraffin-embedded tissue sections after formalin fixation. In human samples, there was a high incidence of autofluorescence+ cells in the 5-HT+ cells in the pyloric, small intestinal and colonic glands, while co-localization was lacking between autofluorescence+ and gastrin+ cells in the pyloric and small intestinal glands. Autofluorescence+ EC cells were detected in the colon of mice and rats. Autofluorescence+ cells were also observed in 5-HT+ β cells in the pancreatic islets of Langerhans in pregnant mice, while non-pregnant mouse pancreatic islet cells showed no 5-HT immunoreactivity or autofluorescence. These results suggest that autofluorescence+ cells are identical to 5-HT+ cells, and the source of autofluorescence may be 5-HT itself or molecules related to its synthesis or degradation. This autofluorescence signal detection method may be applicable for monitoring of inflammatory status of inflammatory bowel diseases in both the experimental and clinical settings.